Effects of a cardiopulmonary rehabilitation programme on submaximal exercise in Tunisian patients with long-COVID19: A randomized clinical trial - Rania Kaddoussi; Hadhemi Rejeb; Amine Kalai; Eya Zaara; Naceur Rouetbi; Zohra Ben Salah Frih; Piotr Zmijewski; Helmi Ben Saad (Biology of Sport)
There is a lack of randomized clinical trials (RCTs) exploring the outcomes of cardiopulmonary rehabilitation programmes (CPRPs) on submaximal aerobic capacity of long COVID-19 patients (LC19Ps). This RCT aimed to evaluate the effect of an ambulatory CPRP on the 6-min walk test (6MWT) data (main outcome: 6-min walk distance (6MWD)) of LC19Ps. Conducted as a single-blinded RCT, the study included Tunisian LC19Ps with persistent dyspnoea (i.e. modified medical research council (mMRC) level ≥2) at least three months postdiagnosis. LC19Ps were randomly assigned to the intervention (IG, n = 20) or control (CG, n = 10) groups. Pre- and post-CPRP evaluations included dyspnoea assessments (Borg and mMRC scales), anthropometric data, spirometry, and 6MWT. The CPRP (i.e. 18 sessions over six weeks) encompassed warm-up, aerobic training, resistance training, respiratory exercises, and therapeutic education. The CPRP significantly improved i) dyspnoea, i.e. IG exhibited larger reductions compared to the CG in Borg (-3.5 ± 2.0 vs. -1.3 ± 1.5) and mMRC (-1.5 ± 0.8 vs. -0.1 ± 0.3) scales, and ii) 6MWD, i.e. IG demonstrated larger improvements compared to the CG in 6MWD (m, %) (168 ± 99 vs. 5 ± 45 m, 28 ± 8 vs. 1 ± 8%, respectively), and resting heart rate (bpm, % maximal predicted heart rate) (-9 ± 9 vs. 1 ± 7 bpm; -5 ± 6 vs. 0 ± 4%, respectively), with small effect sizes. In the IG, the 1.5-point decrease in mMRC and the 168 m increase in 6MWD exceeded the recommended minimal clinical important differences of 1 point and 30 m, respectively. CPRP appears to be effective in enhancing the submaximal exercise capacity of LC19Ps, particularly in improving 6MWD, dyspnoea, and resting heart rate. RCT registration: www.pactr.org; PACTR202303849880222.